A peptide-based fluorescent chemosensor for measuring cadmium ions in aqueous solutions and live cells. Issue 41 (28th September 2015) - Wang, Peng; Wu, Jiang; Liu, Lixuan; Zhou, Panpan; Ge, Yushu; Liu, Dan; Liu, Weisheng; Tang, Yu
Abstract : A novel peptide fluorescent chemosensor (H 2 L ) has been designed and synthesized by solid phase peptide synthesis, which is a promising analytical tool for detecting Cd 2+ in 100% aqueous solutions and live cells. Abstract : A novel peptide fluorescent chemosensor (H 2 L ) with a lysine backbone and both –NH2 sites conjugated with cysteine and dansyl groups has been designed and synthesized by solid phase peptide synthesis with Fmoc chemistry. This chemosensor is a promising analytical tool for detecting Cd 2+ based on the photo-induced electron transfer (PET) effect by turn-on response in 100% aqueous solutions. As designed, H 2 L exhibits excellent cell permeation and low biotoxicity as well as displaying relatively high selectivity and sensitivity. The chemosensor penetrated live HeLa cells and detected intracellular Cd 2+ by turn-on response. The binding stoichiometry and affinity, interference test, pH sensitivity, fluorescence quantum yield, quantum mechanical calculations, lifetimes, and cytotoxicity of the chemosensorH 2 L to Cd 2+ were also investigated. Moreover, H 2 L exhibits low biotoxicity with a limit of detection (LOD) for Cd 2+ of about 52 nM, implying thatH 2 L can be used as a highly selective and sensitive peptide fluorescent chemosensor in biological systems.